Psychometric characteristics of the improved four-factor coping with stress questionnaire - Valickas, Gintautas; Želvienė, Paulina; Grakauskas, Žygimantas (Psichologija, 2010)
The article presents the process of improving the Lithuanian coping with stress questionnaire (Grakauskas ir Valickas, 2006). To assess the reliability and construct validity of the four-factor questionnaire, three studies with the participation of 831 respondents were conducted. The respondents were students of Vilnius University (average age 21.04 years) and of Vilnius gymnasiums (average age 16.42 years). In the first study, the questionnaire was submitted to 417, in the second study to 103 and in the third study to 311 respondents. In the first and second studies, statements of the questionnaire were improved, and the four-factor structure of the questionnaire was assessed. In the third study we assessed some psychometrical characteristics of the questionnaire. The following indexes of scales’ internal reliability (Cronbach’s alpha) were found: social support (α = 0.864), problem solving (α = 0.760), emotional venting (α = 0.692), avoidance (α = 0.661). The test–retest score reliability (Pearson’s correlation coefficients) varied from 0.630 (avoidance scale) to 0.802 (social support scale) (test–retest time interval was two weeks). It has been established that four factors of the questionnaire explained 48.504 per cent of data dispersion. The exploratory factor analysis also indicated a satisfactory suitability of scale items (factor loadings varied from 0.415 to 0.832). Confirmatory factor analysis data indicate a satisfactory suitability of the model of four factors (χ² = 287.58, df =74; RMSEA = 0.077; GFI = 0.93; CFI = 0.87; NFI = 0.84). A correlation between the four-factor coping with stress questionnaire and the COPE questionnaire was also assessed. The Pearson’s correlation indexes between similar scales of the two questionnaires varied from 0,360 to 0,809. Differences were also found between age and gender. University students used the problem solving and social support stress coping strategy more often than gymnasium students, while women used the social support, avoidance and emotional venting stress coping strategy more often than men.
Keywords: coping with stress; reliability and validity of the four-factor coping with stress questionnaire